2020
DOI: 10.1093/pcp/pcaa107
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Carbonyl Species Mediate Methyl Jasmonate-Induced Stomatal Closure

Abstract: Production of reactive oxygen species (ROS) is a key signal event for methyl jasmonate (MeJA)- and abscisic acid (ABA)-induced stomatal closure. We recently showed that reactive carbonyl species (RCS) stimulates stomatal closure as an intermediate downstream of hydrogen peroxide (H2O2) production in the ABA signaling pathway in guard cells of Nicotiana tabacum and Arabidopsis thaliana. In this study, we examined whether RCS functions as an intermediate downstream of H2O2 production in MeJA signaling in guard c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…GSH is thus required downstream of ROS. Consistently, RCS production triggered by MeJA induced GSH depletion in guard cells [ 19 ], indicating that RCS targets likely lie downstream of H 2 O 2 production by RbohD and RbohF proteins in the guard cells.…”
Section: The Implication Of Protein Carbonylation In Phytohormone Signaling Pathwaysmentioning
confidence: 80%
See 4 more Smart Citations
“…GSH is thus required downstream of ROS. Consistently, RCS production triggered by MeJA induced GSH depletion in guard cells [ 19 ], indicating that RCS targets likely lie downstream of H 2 O 2 production by RbohD and RbohF proteins in the guard cells.…”
Section: The Implication Of Protein Carbonylation In Phytohormone Signaling Pathwaysmentioning
confidence: 80%
“…Similar to ABA-induced stomatal closure, the production of ROS by NAD(P)H oxidases is also required by MeJA-induced stomatal closure in A. thaliana guard cells [ 182 , 183 , 184 , 185 , 186 ]. As with ABA, the application of MeJA induced the accumulation of RCS such as acrolein and HNE in WT tobacco plants, thus implicating RCS in MeJA-induced stomatal closure [ 19 ]. A study by Akter and colleagues revealed that stomatal closure induced by MeJA is accompanied by depletion in the level of intracellular GSH found in Arabidopsis guard cells [ 187 ], but no effect of GSH was found in MeJA-induced ROS production [ 188 ].…”
Section: The Implication Of Protein Carbonylation In Phytohormone Signaling Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations